Biomass yield and carbon sequestration after six years of Bombax ceiba L. plantations in relation to stand density - Devi, Rodda Chandana; Das, D.K. (Indian Journal of Agroforestry, 2021)
Tree based land use practice is seen as one of the viable alternatives in mitigating the diverse effect of environmental degradation. A study was conducted to assess the carbon sequestration rate (CSR) and biomass carbon storage potential of six year-old Bombax ceiba L. plantations established at four different plant spacing (5× 2, 5× 3, 5× 4 and 5× 5 m) in calcareous soil of north Bihar. Morphometric measurements of the tree in terms of height, diameter at breast height (DBH) and crown width were recorded. Trees under two wider spacing (400 and 500 trees ha-1) showed height and DBH values on an average 19 and 26% higher than the narrow spacing (1000 and 666 trees ha-1), respectively. Volumes of the stem were also found significantly superior under lower density of the plantation. The highest total biomass (26.5 Mg ha-1) was recorded in the plantation spaced at 5× 2 m, followed by the biomass (25.8 Mg ha-1) of the plantation with the spacing 5× 4 m. Total tree carbon stock ranged from 10.0 Mg ha-1 in plantation with 5× 3 m to 12.6 Mg ha-1 in plantation with 5× 2 m spacing. The highest CSR (1.53 Mg ha-1 year-1) was recorded in plantations with 5× 2 and 5× 4 m. Findings of this study suggest that the maximum amount of biomass (ha-1) is distributed to the stem biomass irrespective of the tree spacing. Among different spacing of plantations, 5× 2 and 5×4 m spacing showed higher amounts of stem biomass as compared to other spacings. Thus, planting of B. ceiba plantation at these spaces must be promoted as a land use practice to help mitigate climate change.